2018
DOI: 10.1007/s11325-018-1619-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sleep hygiene training given to pregnant women with restless leg syndrome on their sleep quality

Abstract: Sleep hygiene training given to pregnant women with restless leg syndrome increased sleep quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…In cross-sectional and longitudinal analyses, poor sleep hygiene resulted a significant predictor of poor sleep, supporting the literature on sleep hygiene as a perpetuating factor of sleep disturbances (Morin 1993, Sönmez & Aksoy Derya, 2018Jung et al 2019;Booker et al 2020). Moreover, cross-sectional correlation analyses showed significant associations between sleep hygiene and anxiety, depression, and stress symptoms.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In cross-sectional and longitudinal analyses, poor sleep hygiene resulted a significant predictor of poor sleep, supporting the literature on sleep hygiene as a perpetuating factor of sleep disturbances (Morin 1993, Sönmez & Aksoy Derya, 2018Jung et al 2019;Booker et al 2020). Moreover, cross-sectional correlation analyses showed significant associations between sleep hygiene and anxiety, depression, and stress symptoms.…”
Section: Discussionsupporting
confidence: 79%
“…Poor sleep hygiene is traditionally considered as a core maintaining factor of chronic insomnia in behavioural (e.g., Spielman et al 1987) and cognitive models (e.g., Morin 1993). Additionally, poor sleep hygiene is involved in the maintenance of other sleep disorders including obstructive sleep apnoea (e.g., Jung et al 2019), shift work disorder (Booker et al 2020), and restless leg syndrome (Sönmez & Aksoy Derya, 2018). Conversely, the implementation of sleep hygiene practices may have the potential to address the public health concern of sleep complaints in the general population (Irish et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“… 10–12 Fortunately, good management of poor sleep during pregnancy can improve maternal and neonatal health. 13–15 …”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Fortunately, good management of poor sleep during pregnancy can improve maternal and neonatal health. [13][14][15] Previous studies showed that age, race, 16 parity, 17 smoking, 18 obesity, 19 physical activity, 22 low income level, third-trimester pregnancy status and insufficient sleep duration 20 were associated with poor sleep during pregnancy. However, to our knowledge, few studies have reported the prevalence and risk factors for poor sleep in different trimesters, especially among Chinese pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of sleep hygiene include avoiding stimulants or disruptive foods near bedtime, daily exercising to promote quality sleep, establishing a relaxing bedtime routine, and creating an optimal sleep environment, among other recommendations. 27 , 28 The addition of sleep hygiene counseling should not pose a substantial additional burden to the provider or any risk to the patient, but could result in improved clinical outcomes. Studies have shown promoting good sleep hygiene to have positive impacts across various populations, particularly in athletes.…”
Section: Discussionmentioning
confidence: 99%